Rome the ultimate empire [videorecording] - Eder, Steve; Westbrook, Joel. (Alexandria, Va. Time Life Video and Television, 1995)
Presents an overview of Roman history and a look on Roman's culture and the activities of the people.
VHS.
Narrated by Sam Waterston.
Keywords: Rome -- History; Rome -- Antiquities